f0=@(m0) (g*m0/c)*(1-e^(-c*t/m0))-v;
Nowhere have you defined e. If you wanted to compute the exponential, instead just call the exp function.
f0 = @(m0) (g*m0/c)*(1-exp(-c*t/m0))-v;
f1=@(m1) (g*m1/c)*(1-e^(-c*t/m1))-v;
f2=@(m2) (g*m2/c)*(1-e^(-c*t/m2))-v;
c=f2; %c value
h0=m1-m0; %h0 value
h1=m2-m1; %h1 value
delta0=(f1-f0)/(m1-m0); %delta0 calculated value
You cannot add or subtract function handles like you're trying to do on the line that defines delta0. You can add or subtract the values you get by evaluating function handles, however.
delta0 = (f1(2)-f0(1))./(m1-m0)
That example subtracts the value of f0 evaluated at m0 = 1 from the value of f1 evaluated at m1 = 2.